Osteology of the Late Triassic Bipedal Archosaur Poposaurus gracilis (Archosauria: Pseudosuchia) from Western North America. Issue 4 (8th December 2019) - Schachner, Emma R.; Irmis, Randall B.; Huttenlocker, Adam K.; Sanders, Kent; Cieri, Robert L.; Nesbitt, Sterling J.
ABSTRACT: Poposaurus gracilis is a bipedal pseudosuchian archosaur that has been poorly understood since the discovery of the holotype fragmentary partial postcranial skeleton in 1915. Poposaurus . gracilis is a member of Poposauroidea, an unusually morphologically divergent clade of pseudosuchians containing taxa that are bipedal, quadrupedal, toothed, edentulous, and some individuals with elongated thoracic neural spines (i.e., sails). In 2003, a well preserved, fully articulated, and nearly complete postcranial skeleton of P . gracilis was discovered with some fragmentary cranial elements from the Upper Triassic Chinle Formation of Grand Staircase‐Escalante National Monument of southern Utah, USA. The aim of this work is to describe the osteology of this specimen in detail and compare P . gracilis to other closely related pseudosuchian archosaurs. The open neurocentral sutures throughout the majority of the vertebral column, the small size of this individual, and the presence of seven evenly spaced cyclic growth marks in the histologically sectioned femur indicate that this specimen was a skeletally immature juvenile, or subadult when it died. The pes of P . gracilis contains multiple skeletal adaptations and osteological correlates for soft tissue structures that support a hypothesis of digitigrady for this taxon. When coupled with the numerous postcranial characters associated with cursoriality, and the many anatomical traits convergent with theropod dinosaurs, this animal likely occupied a similar ecological niche with contemporaneous theropods during the Late Triassic Period. Anat Rec, 303:874–917, 2020. © 2019 American Association for Anatomy